Arrangement Free Wireless Power Transfer via Strongly Coupled Electrical Resonances - Bonyoung Lee; Jungho Kim; Hyunkyeong Jo; Hyungki Min; Franklin Bien (Advanced Science)
Abstract Research on magnetically resonant wireless power transfer (MRWPT) is actively pursued for diverse applications. Dependent on magnetic fields for wireless power transfer (WPT), MRWPT encounters a challenge due to the absence of monopole magnetic properties, impacting power transfer efficiency (PTE) sensitivity to receiver arrangement. Despite extensive research, achieving the desired receiver freedom remains a persistent challenge—a core limitation rooted in magnetic field‐based WPT. To address this, electrically resonant wireless power transfer (ERWPT) is proposed, utilizing an open bifilar coil at a resonant frequency. Experimental results demonstrate nonradiative power transfer of up to 50 watts and 46% PTE over a distance of 2 meters, maintaining consistent PTE performance. This phenomenon arises from the electric charge's monopole capability, distinguishing it from the limitations associated with magnetic fields. The practical viability of this system is delved and suggest directions for further investigation. ERWPT overcomes MRWPT challenges, ensuring lateral plane consistent efficiency and offering a breakthrough for practical wireless power applications.